STUDENTS’ PERCEPTIONS ON THE IMPLEMENTATION OF BLENDED LEARNING IN ENGLISH EDUCATION - Aulia Septi Cahyani Tariah; Anjar Kusuma Dewi; Andi Patmasari; Sriati Usman (e-Journal of ELTS (English Language Teaching Society), 2026)
The purpose of this study was to analyze students' perceptions on the implementation of blended learning in the English Language Education Study Program at Tadulako University. This study involved 100 students from the class of 2024 to explore students' views regarding the implementation of blended learning. The research findings indicate that students have fairly moderate views on blended learning in the context of English language learning. They believe that blended learning stimulates active engagement, communication, and critical thinking. Furthermore, students perceived several benefits, particularly related to the integration of online assignments and contributions from classmates in understanding new material. On the other hand, students also faced several challenges, such as ineffective online interactions, difficulty maintaining focus during online sessions, limited participation in online discussions, and the need for longer time to complete assignments. Some students also felt that blended learning did not fully improve their interpersonal communication and understanding of English language learning materials. In conclusion, blended learning brings both positive and negative aspects to the English language learning process. Therefore, improvements in interaction, participation, focus, and material understanding are needed to improve blended learning effectiveness.